Comparative analysis of forest fuel beds in a mangrove ecosystem - Barrios-Calderón, Romeo de Jesús; Infante Mata, Dulce; Flores-Garnica, José Germán; Jozeph de Jong, Bernardus Hendricus; Monzón Alvarado, Claudia; Maza Villalobos Méndez, Susana (Instituto de Ecología, A.C., 2020)
The evaluation of the complex of forest fuels in forests and jungles constitutes an extremely important advance for the prediction, analysis and control of forest fires. With the objective of characterizing the fuel beds in mangroves of the El Castaño wetland system, La Encrucijada, Chiapas, field measurements were applied and relational data analysis techniques. With this, some indices were calculated for the structure and composition of the forest fuel beds. The biomass of live fuels was quantified using allometric equations; the dead fuels were evaluated applying the planar intersection technique. In this study beds of forest fuels were defined in four types of mangrove, with Rhizophora mangle and Laguncularia racemosa being the most important species in terms of dominance. Canopy fuels in the mangrove of R. mangle presented the highest loads, of biomass (266.67 t ha-1 + 39.58 t ha-1). For dead fuels, there were significant differences in the fuel load of 10 h, being greater in the L. racemosa mangrove swamp (17.21 t ha-1 + 1.11 t ha-1), which represent the greatest potential for the propagation of fire in periods of drought and high temperature. There were no differences in the total load of dead fuels; therefore, the four types of mangrove evaluated have the same capacity to accumulate dead biomass. The results obtained are essential to define the danger of fires.